2009
DOI: 10.1007/s10562-009-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Evidence on the Role of the Nucleophilic Intermediate Complex in the Orito-Reaction: Unexpected Inversion in the Enantioselective Hydrogenation of 2,2,2-Trifluoroacetophenone on Pt-Cinchona Chiral Catalyst Using Continuous-Flow Fixed-Bed Reactor

Abstract: The enantioselective hydrogenation of 2,2,2,-trifluoroacetophenone over Pt/Al 2 O 3 catalysts modified by cinchona alkaloids was investigated for the first time using continuous-flow fixed-bed reactor system in toluene/AcOH 9/1 solvent mixture in absence and presence of 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
(87 reference statements)
3
11
0
Order By: Relevance
“…The STM data provide additional insight into reports in the catalysis literature [13][14][15][16][17] that the presence of small amounts of TFA in toluene gives rise to an increase in the ee and a decrease in the reaction rate in the hydrogenation of TFAP over CD modified Pt. We propose that these changes are caused, at least in part, by the disruption by TFA of aryl-CHÁÁÁO interactions revealed by the STM images in Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The STM data provide additional insight into reports in the catalysis literature [13][14][15][16][17] that the presence of small amounts of TFA in toluene gives rise to an increase in the ee and a decrease in the reaction rate in the hydrogenation of TFAP over CD modified Pt. We propose that these changes are caused, at least in part, by the disruption by TFA of aryl-CHÁÁÁO interactions revealed by the STM images in Fig.…”
Section: Resultssupporting
confidence: 58%
“…As part of a set of systematic tests, they used toluene with added TFA as the solvent and cinchonidine (CD) as the modifier. Among many intriguing results, they confirmed that (i) addition of small amounts of TFA significantly increased the ee and (ii) they found that the conversion rates were lower in the presence of TFA [15][16][17]. Our study was performed by taking scanning tunneling microscopy (STM) measurements for the coadsorption of TFA and TFAP on Pt(111) under ultrahigh vacuum conditions.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…[112][113][114] Several other examples describing enantioselective hydrogenations carried out in commercial and non-commercial continuous flow reactors have been reported in the literature. Among them, the hydrogenation of methyl/ethyl pyruvate [38,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130] ketopantolactone, [116,117,119] 2,2,2-trifluoroacetophenone, [121,122,131,132] isopropyl 4,4,4-trifluoroacetoacetate, [133] 1-phenyl-1,2-propanedione, [134] methyl/ethyl benzoylformate, [116,117,125,135] ethyl-2-oxo-4-phenylbutyrate [136] and 4-methoxy-6-methyl-2-pyrone, [137] should be mentioned. Bartok and co-workers investigated the Pt/Al 2 O 3 -cinchonidine catalyzed enantioselective hydrogenation of ethyl pyruvate (Scheme 10 b), ketopantolactone and methyl benzoylformate using a continuous flow fixed-bed reactor system.…”
Section: Enantioselective Hydrogenationmentioning
confidence: 99%
“…Supposedly, in the hydrogenation of 2,2,2-trifluoroacetophenone the reaction route involves an equilibrium of electrophilic and nucleophilic intermediate complexes, depending on the acid strength and concentration. [131,132] Ketopantolactone and isopropyl 4,4,4-trifluoroacetoacetate (Scheme 11 a) were hydrogenated in a fixed-bed reactor over cinchonidine -modi- www.chemsuschem.org fied Pt/Al 2 O 3 catalyst resulting in 83 % and 90 % ee respectively. [119,133] During the enantioselective hydrogenation of 1-phenyl-1,2-propanedione, the enantioselectivity of the resulting (R)-1-hydroxy-1-phenylpropanone proved to be independent of the reactant concentration and gave comparable enantiomeric excess values (60 %) for both the continuous-flow and batch experiments.…”
mentioning
confidence: 99%